Integrating Macrophages into Organotypic Co-Cultures: A 3D In Vitro Model to Study Tumor-Associated Macrophages - Linde, Nina; Gutschalk, Claudia M.; Hoffmann, Claudia; Yilmaz, Dilan; Mueller, Margareta M. (PLOS ONE, 2012)
Tumor progression is controlled by signals from cellular and extra-cellular microenvironment including stromal cells and the extracellular matrix. Consequently, three-dimensional in vitro tumor models are essential to study the interaction of tumor cells with their microenvironment appropriately in a biologically relevant manner. We have previously used organotypic co-cultures to analyze the malignant growth of human squamous cell carcinoma (SCC) cell lines on a stromal equivalent in vitro. In this model, SCC cell lines are grown on a collagen-I gel containing fibroblasts. Since macrophages play a critical role in the progression of many tumor types, we now have expanded this model by integrating macrophages into the collagen gel of these organotypic tumor co-cultures. This model was established as a murine and a human system of skin SCCs. The effect of macrophages on tumor progression depends on their polarization. We demonstrate that macrophage polarization in organotypic co-cultures can be modulated towards and M1 or an M2 phenotype by adding recombinant IFN-γ and LPS or IL-4 respectively to the growth medium. IL-4 stimulation of macrophage-containing cultures resulted in enhanced tumor cell invasion evidenced by degradation of the basement membrane, enhanced collagenolytic activity and increased MMP-2 and MMP-9. Interestingly, extended co-culture with tumor cells for three weeks resulted in spontaneous M2 polarization of macrophages without IL-4 treatment. Thus, we demonstrate that macrophages can be successfully integrated into organotypic co-cultures of murine or human skin SCCs and that this model can be exploited to analyze macrophage activation towards a tumor supporting phenotype.